2021
DOI: 10.1007/s11010-021-04232-z
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of neopterin in Covid-19: a new perspective

Abstract: Neopterin (NPT) is a member of pteridines group, synthesized by macrophages when stimulated by interferon gamma (INF-γ). NPT is regarded as a macrophage stimulation indicator, marker of cellular immune activation and T helper 1 (Th1) type 1 immune response. Here, we aimed to provide a view point on the NPT features and role in Covid-19. Serum NPT level is regarded as an independent prognostic factor for Covid-19 severity, with levels starting to increase from the 3rd day of SARS-CoV-2 infection, being associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 57 publications
0
71
0
Order By: Relevance
“…Regarding the development of hypoxia in Covid-19, at first, pulmonary vasoconstriction is developed due to high circulating Ang II, leading to high pressure in the pulmonary vessels and leakage of fluids into the alveoli causing pulmonary edema and atelectasis with the development of ARDS [ 69 ]. As a result, left to right shunting (LRS) will develop, causing an incomplete gas exchange and persistence hypoxia not responding to the oxygen supplement [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the development of hypoxia in Covid-19, at first, pulmonary vasoconstriction is developed due to high circulating Ang II, leading to high pressure in the pulmonary vessels and leakage of fluids into the alveoli causing pulmonary edema and atelectasis with the development of ARDS [ 69 ]. As a result, left to right shunting (LRS) will develop, causing an incomplete gas exchange and persistence hypoxia not responding to the oxygen supplement [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…High NLR is correlated with underlying inflammatory reactions and is an independent risk factor for Covid-19 severity [30] . In SARS-CoV-2 infection, different chemokines and cytokines that act as NTs attractants are elevated primarily in patients with severe Covid-19, suggesting the possible role of the NTs against SARS-CoV-2 [31] . It has been reported that the lungs autopsies of patients with Covid-19 have high NTs infiltrations characterized by neutrophilic mucositis, acute capillaritis, and fibrin deposition with neutrophilic extravasations into the air space [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Keidar et al ( 2005 ) illustrated that aldosterone antagonist eplerenone improves cardiac contractility through augmentation expression of ACE2, which increase the protective Ang1-7 and reduces harmful AngII (Keidar et al 2005 ). These findings may explain the protective role of ACEIs and ARBs against SARS-CoV-2 infection-induced acute cardiac injury through overexpression of cardiac ACE2 (Al-kuraishy et al 2021d ). Moreover, in HF, chymase activity is increased, leading to elevation of AngII and reduction of Ang 1-7.…”
Section: Covid-19 and Risk Of Heart Failurementioning
confidence: 99%